Romantika Sastra dan Estetika Terjemahan: Analisis Estetik-Semantik terhadap Risālah Bāhitsatul Bādiyah (37 H) Karya Malak Hifni Nashif - Sutobri, Viyan; Sefira, Lutfiana; Farhan Y.Z.L, Muhammad; Ansori, Muhammad (STAINI Press, 2025)
This article examines how the aesthetic-semantic approach in literary translation preserves beauty, symbolism, and emotion in Risālah Bahitsatul Bādiyah, a classical Arabic mahfudzat rich in poetic and reflective values. The study focuses on the application of communicative translation and Larson’s translation model to ensure fidelity of message and aesthetic quality in the target language. Using a descriptive-qualitative method with stylistic and semantic analysis, this research demonstrates that effective literary translation must go beyond literal accuracy to reconstruct the writer’s emotional atmosphere and cultural context for modern Indonesian readers. The process of Analyze–Transfer–Restructure plays a crucial role in maintaining the poetic soul of the text while adapting it to the target culture. The findings emphasize that aesthetic goals are dominant in translating this text, as the strength of Risālah Bahitsatul Bādiyah lies in its emotional depth and artistic expression.